Deviations in Islamic Scientific Orientation Through Secularism - Siti Mursalina; Maspuroh; Rismayanti; Rizqi Nazwa Ramdhani (Al-Iffah: Journal of Islamic Sciences Research, 2025)
This study is motivated by the existence of secularism among Indonesian citizens in political affairs. To respond to this, the author conducts a review that aims to draw new conclusions and solutions that can be produced. The purpose of this paper is to find out the relationship between secularism and Islamic scientific orientation. This research is a qualitative research with theoretical studies using William Manning's opinion. This research was conducted on several Indonesians who were in the campus environment of STAI Al Azhary Cianjur. This research aims to find and study the speakers' opinions about secularism and its relation to Islamic scientific orientation. The results showed that there were still differences of opinion in viewing secularism, but there was a development of knowledge put forward by the speakers which became evidence in Islamic scientific orientation.